Effects of catalytic bed position on hydrogen production by methane decomposition - Sikander, U. (Universiti Malaysia Pahang, 2018)
COx free hydrogen can be produced by thermal decomposition of methane. Such process is carried out in a fixed bed catalytic reactor. Where heterogeneous catalytic reaction occur when methane come in contact with catalyst bed at a temperature range of 650-900ºC. In this work effect of different catalyst bed positions are investigated on the overall methane conversion to hydrogen. Experimental studies are carried out to in a Fixed Bed Reactor at 700oC, by placing a catalyst bed of same porosity µ=0.2 at 25, 50, 75 column height, and at top of reactor. It is found that same catalyst has shown different results when placed at different heights in reactor column. Highest methane conversion of 85 is found when catalyst bed is placed at 25 column height from bottom. It is found that for endothermic reactions like methane decomposition catalyst bed position has its significance due to its effects on process thermal conditions and on bed expansion by carbon deposition. © Universiti Malaysia Pahang, Malaysia